Estudo exploratório e descritivo sobre inclusão familiar de crianças com surdocegueira pré-linguística - Ikonomidis, Vula Maria (2009)
Deafblindness is a single impairment that brings implications in the development of the person, and communication is the main issue as well as the fact that it is necessary a specific intervention so that the person with deafblindness can acquire language. It is important that the families receive proper orientation about how to deal with his or her child. Several studies in this area confirm the benefits of intervention programs in the family dynamics. However, there are few studies in Brazil, so an exploratory and comparative research was found to be necessary. The studies about family and deafblindness focus either on the needs and expectations of the families or on intervention programs. This study has had the goal to analyze forms of communication between caregivers and children and compare with the level of participation of the child in the family, divided into two groups: a) children who were still not in a specialized program and b) children who already attended in a specialized program in deafblindness. Each group was formed by three dyads (mother or primary caregiver and child). The following instruments were used to collect data: the Home Environment Resources Scale (RAF); a protocol of observation; PAVII-PAN (Parents and Visually Impaired Infants); and documents analysis. The interviews were taped or recorded on video and the data analysis categorized into the following: a) documents; b) data obtained from RAF; c) description of the direct observations and films; d)data obtained from PAVII-PAN. A triangulation to interpret the data was performed. The results show that the children in the group that already attend specialized programs have more concrete and symbolic communication skills while the children from the other group make use of basically corporal communication, with a limited use of functions for immediate needs and protest. As final considerations one can infer that even the families who do not use an effective communication try to include the child in the activities that the whole family take part, but still the same children cannot yet enjoy entirely of such interactions and inclusion because they cannot express more than what is immediate, and also for a possible lack of total understanding of what happens around him or her. Programs of public policies are recommended to provide social and emotional support and the systematization of interventives programs using tools that will make possible the collaboration between family and professionals in order to improve the quality of life of the children with deafblindness in Brazil.